Generalized Derivations of BCC-Algebras - S. M. Bawazeer; N. O. Alshehri; Rawia Saleh Babusail (International Journal of Mathematics and Mathematical Sciences, 2013)
The notion of generalized derivations of BCC-algebras is introduced, and some related properties are investigated. Also, we consider regular generalized derivations and the D-invariant on ideals of BCC-algebras. We also characterized KerD by generalized derivations.